The Sea Harvest Ritual as A Basis for Ecological Education and Climate Resilience in The Coastal Communities of Probolinggo - Lestari, Wahyu; aziz, Abd; Rachman, Poppy (Proceedings of Annual Conference for Muslim Scholars, 2025)
The present inquiry investigates the Petik Laut ritual, a foundational tradition of local wisdom among the coastal communities of Probolinggo, East Java. This ceremony, which expresses gratitude for marine abundance and maritime safety, reflects a profound ecological and spiritual nexus between the community and the sea. This article seeks to explore the ecopedagogical values embedded in the ritual and its strategic relevance to ecological education and climate resilience. Utilizing a descriptive qualitative approach with an ethnographic method, the investigation gathered data through participant observation and in-depth interviews with traditional leaders and local fishermen. The findings reveal that Petik Laut serves as a vital informal educational medium, fostering ecological awareness through sea-cleaning initiatives and environmentally conscious Larung Sesaji (offering) practices. Furthermore, the ritual strengthens social solidarity and environmental ethics, while climate adaptation is manifested through the traditional scheduling of ceremonies based on seasonal weather patterns. The current analysis concludes that preserving Petik Laut provides a robust foundation for culture-based ecological education, offering a localized model for strengthening adaptive resilience against contemporary environmental challenge